Bispecific Aptamer Chimeras Enable Targeted Protein Degradation on Cell Membranes. (7th April 2021) - Miao, Yanyan; Gao, Qianqian; Mao, Menghan; Zhang, Chao; Yang, Liqun; Yang, Yang; Han, Da
Abstract: The ability to regulate membrane protein abundance offers great opportunities for developing therapeutic sites for various diseases. Herein, we describe a platform for the targeted degradation of membrane‐associated proteins using bispecific aptamer chimeras that bind both the cell‐surface lysosome‐shuttling receptor (IGFIIR) and the targeted membrane‐bound proteins of interest. We demonstrate that the aptamer chimeras can efficiently and quickly shuttle the therapeutically relevant membrane proteins of Met and PTK‐7 to lysosomes and degrade them through the lysosomal protein degradation machinery. We anticipate that our method will provide a universal platform for the use of readily synthesized aptamer materials for biochemical research and potential therapeutics. Abstract : Bispecific aptamer chimeras were designed and constructed for lysosomal degradation of targeted membrane‐associated proteins (see picture). The method provides a powerful and potentially universal platform for the use of inexpensive and readily synthesized aptamer materials for the clinical translation of nucleic‐acid‐based molecular medicine.